2016
DOI: 10.1055/s-0042-116112
|View full text |Cite
|
Sign up to set email alerts
|

Common Cold – an Umbrella Term for Acute Infections of Nose, Throat, Larynx and Bronchi

Abstract: Acute respiratory tract infections, i. e. rhinitis, sinusitis, pharyngitis, laryngitis, bronchitis, belong to the most common medical conditions with a high economic burden. Nonetheless, there is little agreement concerning their differential diagnosis.This paper will discuss to what extent different anatomical sites of acute respiratory tract infections can be uniquely identified or whether the overlap and consecutive development in signs and symptoms renders these distinctions meaningless.Acute respiratory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 35 publications
(30 reference statements)
0
24
0
4
Order By: Relevance
“…Besides common pharyngitis symptoms such as sore throat, cough and fever [ 1 , 2 ], we also included other search terms during the analysis. Common cold is an often-used umbrella term for acute infections of the upper respiratory tract including acute pharyngitis [ 32 ]. Similarly, incidence peaks for these medical conditions occur mostly during the winter months [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides common pharyngitis symptoms such as sore throat, cough and fever [ 1 , 2 ], we also included other search terms during the analysis. Common cold is an often-used umbrella term for acute infections of the upper respiratory tract including acute pharyngitis [ 32 ]. Similarly, incidence peaks for these medical conditions occur mostly during the winter months [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…URIs are mainly caused by viruses, including rhinovirus, coronavirus, respiratory syncytial virus and so on [7] , [8] , [9] . Following virus infections, bacterial colonization may occur in some cases, which aggravates the disease and leads to prolonged recovery [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Viral infections of the respiratory tract are also common in all age groups and are the leading cause of mortality in children under 5 years of age in developing countries [2]. They pose a significant symptom burden for individuals and a high financial burden to societymostly due to loss of productivity, healthcare costs, and school absenteeism [3]. Advances in diagnostic testing and improved ability to detect pathogens have demonstrated that viral pathogens are important causal pathogens of respiratory tract infection even in immunocompetent patients.…”
Section: Definition/backgroundmentioning
confidence: 99%
“…Additionally, viral respiratory infections play an important role as a trigger for exacerbations of chronic respiratory diseases, such as asthma, or chronic obstructive pulmonary disease (COPD) [3].…”
Section: Definition/backgroundmentioning
confidence: 99%